Participação e conhecimentos femininos na inserção de novas espécies de pescado no mercado e na dieta alimentar dos pescadores da RESEX Mãe Grande em Curuçá/PA - PALHETA, Marllen Karine da Silva (Universidade Federal do Pará, 2014)
This paper aims to describe the main as the traditional knowledge of women shellfish and fisher of river and sea, the locality of Caratateua, RESEX Marine Mom Large Curuçá – PA, contributes to market integration and commercialization of new species of fish. Therefore, the paper uses a methodology qualitative and quantitative, disposing of data that point to a scarcity of the species is much appreciated in the local market, as well as presents the knowledge traditional female on key species that comprise the diet of fishermen as a way to bring new species in the local market. The paper describes, more, species that have been entered into the system from the feminine knowledge. Data collection occurred in the period from March to August 2012. The methodological techniques were semi-structured interviews and participant observation. To characterize the community socioeconomically were applied 76 questionnaires with residents. The semi-structured interviews were conducted with fishers / seafood community, being applied 10 questionnaires and market in the city of Curuçá were applied 9 questionnaires sent to sellers of fish. The interviews showed the changes over the years, evidencing the shortage of traditional species, both the table fisherman as the consumer market. Stresses, especially, as the woman has a fundamental role in inclusion of new species in both sectors, because there is a greater perception about the natural resources consumption.